MENANAMKAN PEMIKIRAN KRITIS KEPADA PESERTA DIDIK SEKOLAH DASAR MELALUI KISAH-KISAH NABI: TRANSFORMASI NILAI ISLAM KE DALAM KETERAMPILAN ABAD 21 - Dinda Rahmah Samoes, Gita Rizky Amelia; Irene Riana Khairunnisa, Rizki Amrillah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Cultivating critical thinking is a major need in 21st century education, where learners are required to be able to analyze, evaluate, and create solutions to complex problems. In the context of Islamic education, the stories of the prophets have great potential as a learning medium that not only conveys moral and spiritual values, but also is able to stimulate students' critical thinking skills. This study aims to explore how the prophet's stories can be used pedagogically to transform Islamic values into 21st century skills, especially critical thinking. The method used is library research with a qualitative approach. The results of the study show that stories such as Prophet Ibrahim, Prophet Moses, and Prophet Muhammad SAW contain narratives that challenge reason, encourage dialogue, and provide space for reflection and decision making that can be developed as teaching materials to practice critical thinking. This integration not only relevates the teachings of Islam with the needs of the times, but also strengthens the character and personality of students as a generation of religious, reflective, and rational learners.